Evaluación y control de ruido ocupacional en la empresa minera de explotación SERINGTELL E.I.R.L. Cobrepampa - Bella Unión – Arequipa 2018 - Tello Chacon, Nestor Mauricio (2020)
An investigation was developed that aimed to evaluate and propose control measures for occupational noise in the workers who work at the mining company SERINGTELL E.I.R.L, this research consists of the identification, measurement and control proposal. As part of the identification we started with an initial inspection of the area to find the places that produced the most noise in the area, after identifying the critical areas we went on to measure the noise they generated for which the sound level meter and the dosimeter were used, In the case of the sound level meter, the measurement with the CYRRUS brand model CR-821 – B was taken. The measurement was taken in the areas of exploitation, machinery, crushing and camping. The results obtained were in the area of exploitation a 98.6dB, the area of machinery 76.8 dB, the crush zone 83.4 dB and in the camp area 53.4 dB. It was possible to identify that the zones that exceeded the allowed according to the regulations of the ECAS are the zone of exploitation and crushing In the case of dosimeter, it was carried out with the CASELLA model CEL -350 model and I take samples in 3 people in different jobs to cover different areas of the company, the positions chosen were the compressor operator, the performer and the sorter mineral, the results that exceeded the regulations were in the position of the compressor operator with an LAeq of 86.2 dB during an 8-hour workday and the performer with an LAeq of 86 dB during an 8-hour workday while the sorter of ore had a LAeq result of 84.3db in a 5-hour workday Once the results were obtained, control measures were determined taking into account the hierarchy of control and the low budget that the company had in the area of safety, a training plan was proposed that consists of a topic on occupational noise, use and care of Hearing protection equipment also proposed the purchase of appropriate protectors for the task they perform.